2020
DOI: 10.1021/acs.cgd.0c00297
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-assisted Cathodic Deposition of Copper-Carboxylate Metal–Organic Framework Films

Abstract: Reductive deposition is an attractive strategy to prepare films of metal–organic frameworks (MOFs), but to cathodically deposit the intergrown dense films of MOFs containing readily reduced metal ions (e.g., Cu2+) without the plating of the corresponding metals still remains a significant challenge. Here, we report the cathodic deposition of metallic copper-free films of two copper-carboxylate MOFs (HKUST-1 and MOF-14). Our strategy relies on the utilization of O2 as probase to electrochemically trigger the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 48 publications
0
37
0
Order By: Relevance
“…In addition, two kinds of copper‐carboxylate MOFs (Cu‐BTC and MOF‐14 [Cu 3 BTB 2 , H 3 BTB = benzene‐1,3,5‐tris(4‐benzoic acid)]) were also prepared without any metallic plating through the oxygen‐assisted cathodic deposition (Figure 11B). 75 The synergistic catalytic effects of the acidic copper ions and BTC ligands on the O 2 reduction can positively shift the deposition potential of Cu‐BTC significantly to +0.05 V (vs. Ag/AgCl 3 mol/L KCl), which is far positive than that of the plating of metallic copper. For the deposition of Cu‐BTC, a dimethyl sulfoxide (DMSO) solution containing 10 mmol/L of Cu(NO 3 ) 2 and 5 mmol/L of H 3 BTC was prepared due to the strong interactions between the DMSO molecules and Cu 2+ as well as the formation of hydrogen‐bonded between DMSO and H 3 BTC, which endows this precursor solution with good stability.…”
Section: Mofsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, two kinds of copper‐carboxylate MOFs (Cu‐BTC and MOF‐14 [Cu 3 BTB 2 , H 3 BTB = benzene‐1,3,5‐tris(4‐benzoic acid)]) were also prepared without any metallic plating through the oxygen‐assisted cathodic deposition (Figure 11B). 75 The synergistic catalytic effects of the acidic copper ions and BTC ligands on the O 2 reduction can positively shift the deposition potential of Cu‐BTC significantly to +0.05 V (vs. Ag/AgCl 3 mol/L KCl), which is far positive than that of the plating of metallic copper. For the deposition of Cu‐BTC, a dimethyl sulfoxide (DMSO) solution containing 10 mmol/L of Cu(NO 3 ) 2 and 5 mmol/L of H 3 BTC was prepared due to the strong interactions between the DMSO molecules and Cu 2+ as well as the formation of hydrogen‐bonded between DMSO and H 3 BTC, which endows this precursor solution with good stability.…”
Section: Mofsmentioning
confidence: 99%
“…Thus, the undercut‐induced detachment in anodic dissolution (vide supra) can be circumvented in cathodic ECD 40 . However, the cathodic ECD needs demanding conditions, otherwise the metal plating will take place simultaneously, which results in the impurity of the as‐synthesized MOFs 70,74,75 NO3+H2normalO+2eNO2+2OH…”
Section: Mofsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Lu et al recently reported the reduction of dissolved molecular oxygen for the deprotonation of carboxylic ligands. [25][26] They achieved the cathodic deposition of Cu-BTC (BTC = benzene-1,3,5-tricarboxylate) in the potential range between À0.1 V and 0.05 V vs. Ag/AgCl at 120 8C by pre-purging the electrolyte with oxygen. [25] Nevertheless, the high temperature, limited solubility of oxygen in aprotic solvents, narrow working potential range and low current density (ca.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26] They achieved the cathodic deposition of Cu-BTC (BTC = benzene-1,3,5-tricarboxylate) in the potential range between À0.1 V and 0.05 V vs. Ag/AgCl at 120 8C by pre-purging the electrolyte with oxygen. [25] Nevertheless, the high temperature, limited solubility of oxygen in aprotic solvents, narrow working potential range and low current density (ca. 0.03 mA cm À2 at À0.1 V vs. Ag/AgCl) due to the low solubility of oxygen in most solvents does not make this method appealing for practical deposition of MOF films.…”
Section: Introductionmentioning
confidence: 99%